Estructura y dinámica sucesional de la regeneración natural en el bosque siempreverde piemontano con intervención de manejo forestal en Zamora Chinchipe, Ecuador - Ramirez Guamán, Tito Germán (2023)
Natural regeneration is the most important ecological process for forest renewal over time. The objectives of this research were to characterize the floristic composition and population structure of regenerating species with forest management intervention, and to evaluate the relationship between environmental factors and the natural regeneration of the evergreen piedmont forest in Zamora Chinchipe. The sampling areas were stratified according to the time after the application of forest management: (T0) reference area; (T5) five years and (T10) ten years. Five sampling units (nested transect) were installed in each forest type. Natural regeneration variables were evaluated: seedlings, saplings and saplings and environmental variables: edaphic and physiographic. For floristic composition and diversity, species rarefaction curves (Hill numbers) and multivariate analysis by dimensional scaling (NDMS) were used. For population structure, we compared the variables of richness, abundance, diameter at base height (DABmm) and height (cm) between T0, T5 and T10. In addition, structural parameters were calculated for each species, such as density, absolute and relative frequency, and the simplified importance value index (IVI). To determine the magnitude of the relationship between regeneration variables (dependent variables) and environmental variables (independent variables), canonical correlation analysis (CCA) and principal component analysis (PCA) were performed. The floristic composition of the total natural regeneration (T0, T5, T10) was 1811 individuals, represented by 125 species, 88 genera and 41 families. We found that there is similarity in the composition of regenerating species (ANOSIM, R= 0,09, p=0,13) in the evergreen piedmont forest. Species abundance and richness showed differences in seedlings (p=0,0036) and saplings (p=0,0144) between T0 and T5; T10. In contrast, there was a difference in species richness (p=0,0079) between T10 and T0; T5 (p<0.05). The CCA determined that the environmental variables that explain the floristic composition in seedlings, saplings and grasslands were altitude; soil depth; clay; pH; Mn, N, P and K being the most influential for the natural regeneration of forests with and without forest management intervention. In conclusion, the structure and diversity of regenerating species is mostly conditioned by the availability of nutrients in the soil and by different environmental variables associated with the dynamics of succession after forest management.